Pyrolysis kinetics of regional agro-industrial wastes using isoconversional methods. Issue 2 (4th March 2019) - Saffe, Alejandra; Fernandez, Anabel; Echegaray, Marcelo; Mazza, Germán; Rodriguez, Rosa
ABSTRACT: The thermochemical conversion, under inert atmosphere, at high heating rate of agro-industrial wastes was studied using thermogravimetric analysis. Two reaction mechanisms were supposed: (a) The thermal solid decomposition is carried out through a single reaction; or (b) this occurs through several independent parallel reactions based on its main components. Kinetic isoconversional methods were applied to both proposed mechanisms. The best fit was obtained for the single-reaction models. Nevertheless, to study the influence of pseudocomponent decomposition in the global process, the kinetic behavior of each of them was analyzed. The R2 and D3 models represent the thermal decomposition of biomass wastes and their pseudocomponents. The first model supposes that the reactions tend at first order, and the second assumes that the diffusion is the predominant phenomenon. In all cases, the model with the best fit for the cellulose decomposition is the same for the single global reaction model. The enthalpy variations are positive, indicating that the reactions are endothermic. The entropy variations have negative values, signifying that these processes are slow. The Gibbs free energy variations exhibited positive values, revealing that the total system energy increased at the approach of the reagents and the formation of the activated complex.